Impact evaluation of a school-based oral health program: Kuwait National Program - Aishah Alsumait; Mohamed ElSalhy; Sahar Behzadi; Kim D. Raine; Rebecca Gokiert; Ken Cor; Sabiha Almutawa; Maryam Amin (BMC, 2019)
Abstract Background This study evaluated the relationship between enrolment in a school-based oral health prevention program (SOHP) and: 1) children's dental health status and oral health-related quality of life (OHRQoL), and 2) mothers' oral health (OH) knowledge, attitude, practice, and OHRQoL. Methods This cross-sectional study, in the Kuwait Capital, included 440 primary school children aged 11 to 12 years and their mothers. Participants were classified into two groups: SOHP and non-SOHP. The SOHP group had been enrolled in the prevention program for at least 3 years: children had twice-a-year applications of fluoride varnish and fissure sealants if needed; mothers had, at least, one oral health education session. The non-SOHP group had negative consents and had not been exposed to the prevention program activities. Dental examinations were performed at schools using portable dental units. Caries experience was determined using the decayed (D/d), missing (M/m), and filled (F/f) teeth (T/t)/surface (S/s) indices. Children's OHRQoL was assessed using a self-administered validated Child Perceptions Questionnaire 11-14 (CPQ11-14). Mothers' OH knowledge, attitude, practice, and OHRQoL were also assessed. After Bonferroni correction, a p-value of less than 0.05 was considered statistically significant for caries experience measures while a p-value of less than 0.013 was considered statistically significant for OHRQoL subscales and mothers' OH knowledge, attitude, practice, and OHRQoL. Results Mean (SD) DT/dt, DMFT/dmft and DMFS/dmfs were 1.41 (1.66), 2.35 (2.33), and 4.41 (5.86) for SOHP children, respectively. For non-SOHP children, the means were 2.61 (2.63), 3.56 (3.05), and 7.24 (7.78), respectively. The difference between the SOHP and non-SOHP was statistically significant (p <  0.001). Children enrolled in the program had a higher number of sealed and restored teeth. No significant differences were found in CPQ11-14 scores or subscale scores between the two groups. No significant difference in mothers' OH knowledge, attitude, practices or OHRQoL was found between SOHP and non-SOHP groups (P > 0.013). Conclusion Enrolment in the SOHP prevention services was associated with a positive impact on children's caries level with no significant impact on mothers' knowledge, attitude, practice, or OHRQoL.